Applications of Nonlinearity in Passive Vibration Control: A Review - Balaji, P. S.; Karthik SelvaKumar, K. (Journal of Vibration Engineering & Technologies, 2021)
Background Vibration present on various levels in many engineering fields and hence vibration mitigation has become a subject of intense study. The nonlinear vibration isolation devices are effective for broad frequency bandwidth and can provide better vibration isolation than linear devices. The need for nonlinearity in stiffness and damping characteristics has motivated researchers to apply the nonlinearity found in mechanisms or materials in the passive vibration control devices. Review Factor This review discusses the applications of nonlinearity in the passive vibration control devices to provide an understanding of how the nonlinearity is applied and useful in the implemented system. Further, applications for nonlinearity can also be extended in the energy harvesting devices, Nonlinear energy sink, metamaterials for the purpose of vibration isolation and energy harvesting. The need for nonlinearity also encouraged research work through inspiration from the nature called bio-inspired devices. The bio-inspired devices mimic the nonlinearity of the biological system to suppress the vibrations. Conclusions The nonlinear passive isolation is effective for wide frequency bandwidth than the linear isolation system. Further, the nonlinear systems also reduce transmissibility much efficiently than the linear system. The nonlinear energy harvesting system shows a great scope to harvest energy from wide ranges of excitations. The bio-inspired devices also are proven to be effective in vibration isolation. Additionally the design of the metamaterial with nonlinearity in the microstructure, proves to be promising in the vibration suppression applications. Based on the review, the nonlinearity introduced into the systems has greater benefits than the linear systems.